2014
DOI: 10.5588/ijtld.13.0854
|View full text |Cite
|
Sign up to set email alerts
|

The effects of statin use on the development of tuberculosis among patients with diabetes mellitus

Abstract: TB development among newly diagnosed type 2 DM was considerable, and statin use among these diabetics was not associated with a protective effect on TB incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 23 publications
1
50
2
Order By: Relevance
“…However, there are significant differences in the study design and results between our study and Kang et al 's study conducted in South Korea. In that study, it was found that the use of statins in patients with diabetes did not affect the risk of active TB (adjusted HR 0.98; 95% CI 0.89 to 1.07) 28. We believe that this finding cannot be applied to the general population because diabetes is associated with a threefold higher risk of TB, as determined by a meta-analysis 29.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, there are significant differences in the study design and results between our study and Kang et al 's study conducted in South Korea. In that study, it was found that the use of statins in patients with diabetes did not affect the risk of active TB (adjusted HR 0.98; 95% CI 0.89 to 1.07) 28. We believe that this finding cannot be applied to the general population because diabetes is associated with a threefold higher risk of TB, as determined by a meta-analysis 29.…”
Section: Discussionmentioning
confidence: 91%
“…Second, we observed that the protective effects of statins are mainly observed in current or chronic users but not in past users. Unfortunately, the different types of statin users were combined in Kang et al 's work 28. Thus, the protective effect of statins might have been overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…107 As adjunctive therapy in murine TB, statins shorten the time to culture negativity by 1 month, reduce tissue pathology, decrease the proportion of culturepositive relapse cases and enhance bacterial killing. [108][109] Statin usage by newly diagnosed type-2 diabetics did however, not prevent development of TB, 110 and further studies are required.…”
Section: Cholesterol-lowering Drugsmentioning
confidence: 99%
“…Treatment with the statin simvastatin (at a dose of 25 mg kg -1 ) was shown to accelerate bacillary clearance in the lungs of mice when administered in combination with standard therapy 106 . However, a large retrospective analysis using a national medical claims database found that statins did not protect against tuberculosis in individuals with diabetes mellitus 107 . Some statins, such as rosuva statin, are not metabolized by CYP3A4 and are therefore unlikely to require dose adjustment due to rifampicin.…”
Section: Other Pde Inhibitorsmentioning
confidence: 99%